Agent-based approaches in economics and social complex systems IX : post-proceedings of the AESCS International Workshop 2015 - Putro, Utomo Sarjono; Ichikawa, Manabu; Siallagan, Manahan (Springer, 2017)
This book includes many cases that provide new perspectives in developing agent-based modeling and simulation. The real problems are complex, and sophisticated methodology is needed to handle them. Agent-based modeling and simulation is one methodology that provides a bottom-up experimental approach applicable to social sciences such as economics, management, sociology, and politics as well as some engineering fields dealing with social activities. However, to improve the applicability of agent-based modeling and simulation methods, a new perspective is needed. In this book, that new perspective is developed and utilized to deal with many cases of real-world problems such as the supply chain, land use and land cover, transportation, health, services, economics, and social problems. The cases are selected from papers presented at the Ninth International Workshop on Agent-Based Approaches in Economic and Social Complex Systems held in Bali, Indonesia, in 2015. At the workshop, 29 reviewed full papers were presented, and of those, 16 were selected to be included in this volume.
Keywords: Economics -- Mathematical models -- Congresses.; Economics -- Computer simulation -- Congresses.; Social sciences -- Computer simulation -- Congresses.; Social sciences -- Mathematical models -- Congresses.; Social systems -- Congresses.; elektronické knihy; electronic books